2020
DOI: 10.3389/fimmu.2020.00929
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Latent Mycobacterium tuberculosis Does Not Affect the Infant Immune Response Following BCG at Birth: An Observational Longitudinal Study in Uganda

Abstract: Background: BCG has low efficacy in tropical countries. We hypothesized that maternal latent Mycobacterium tuberculosis (M.tb) infection (LTBI) results in fetal tolerance to mycobacterial antigens and impaired responses to BCG immunization. Methods: We enrolled 132 LTBI-positive and 150 LTBI-negative mothers and their babies in Entebbe, Uganda. Infants were BCG-immunized at birth. Cord blood and samples at weeks 1, 4, 6, 10, 14, 24, and 52 were analyzed for cytokine/chemokine responses to M.tb antigens by Lumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 40 publications
1
22
0
1
Order By: Relevance
“…There was also no difference in IL-2, IFN-γ, TNF-α, and/or IL- 17-expressing subsets of CD4, CD8 and γδ T-cells between IGRA+ and IGRA- South African adults following 12 h of BCG stimulation, nor correlations with MTB growth in a cross-sectional study [48] . Cytokine responses to MTB antigens of samples from babies born to mothers with or without LTBI also do not differ [57] .…”
Section: Discussionmentioning
confidence: 93%
“…There was also no difference in IL-2, IFN-γ, TNF-α, and/or IL- 17-expressing subsets of CD4, CD8 and γδ T-cells between IGRA+ and IGRA- South African adults following 12 h of BCG stimulation, nor correlations with MTB growth in a cross-sectional study [48] . Cytokine responses to MTB antigens of samples from babies born to mothers with or without LTBI also do not differ [57] .…”
Section: Discussionmentioning
confidence: 93%
“…The ESAT6/CFP10-expressing NTM such as M. szulgai (30) have previously been identified in Ugandan infants and adolescents where the overall prevalence of NTM in infants from rural Uganda investigated for pulmonary tuberculosis was 3.7% (31). We were interested in whether the differences observed for overall median responses to mycobacterial antigens between Ugandan and UK infants were influenced by maternal LTBI exposure of Ugandan infants, though we recently demonstrated that, in Uganda, maternal LTBI does not influence infant responses to BCG immunization (17). Similarly, in this analysis we did not find differences in the immune response between infants of mothers with and without a LTBI for most cytokines except for IL-10, IL-13, and IL-8 responses to ESAT6/CFP10 stimulation that were higher in UK infants than in Ugandan infants of mothers without LTBI, at 10 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Between June 2014 and October 2016, healthy Ugandan mothers and their infants were recruited at Entebbe General Hospital as part of a larger study to investigate the impact of maternal LTBI on the infant response to BCG immunization ( 17 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations